Managerial Model Analysis of School Principles in Improving Student Character in Junior High School Panca Budi Medan - Rita Nofianti; Rika Widya; Salma Rozana; Munisa Munisa (Budapest International Research and Critics University, 2021)
The problem in this research is the analysis of school readiness in facing learning in the millennial era. The purpose of this study: To determine the readiness of schools in facing learning in the millennial era at SMK Panca Budi 2 Medan FY 2019/2020. qualitative research and to determine the sample in this study using purposive sampling totaling 60 students from class XI AK and XII PS. Data collection techniques were carried out using observation and interviews with the students concerned and people who could provide the information under study. The data analysis technique in this study uses data reduction, data presentation and conclusion drawing. From the results of the study, it can be seen that the readiness of schools in facing learning in the millennial era at SMA Panca Budi 2 Medan T.A 2019/2020 has been going well. In terms of school readiness in facing learning in the millennial era at the PANCA BUDI 2 Medan school, there is 80% readiness. And 20% are in a state that is not ready to face learning in the millennial era.